Biological sources of inflexibility in brain and behavior with aging and neurodegenerative diseases - Hong, S. Lee; Rebec, George V. (Frontiers in Systems Neuroscience, 2012)
Almost unequivocally, aging and neurodegeneration lead to deficits in neural information processing. These declines are marked by increased neural noise that is associated with increased variability or inconsistency in behavioral patterns. While it is often viewed that these problems arise from dysregulation of dopamine (DA), a monoamine modulator, glutamate (GLU), an excitatory amino acid that interacts with DA, also plays a role in determining the level of neural noise. We review literature demonstrating that neural noise is highest at both high and low levels of DA and GLU, allowing their interaction to form a many-to-one solution map for neural noise modulation. With aging and neurodegeneration, the range over which DA and GLU can be modulated is decreased leading to inflexibility in brain activity and behavior. As the capacity to modulate neural noise is restricted, the ability to shift noise from one brain region to another is reduced, leading to greater uniformity in signal-to-noise ratios across the entire brain. A negative consequence at the level of behavior is inflexibility that reduces the ability to: 1) switch from one behavior to another; and 2) stabilize a behavioral pattern against external perturbations. In this paper, we develop a theoretical framework where inflexibility across brain and behavior, rather than inconsistency and variability is the more important problem in aging and neurodegeneration. This theoretical framework of inflexibility in aging and neurodegeneration leads to the hypotheses that: 1) dysfunction in either or both of the DA and GLU systems restricts the ability to modulate neural noise; and 2) levels of neural noise and variability in brain activation will be dedifferentiated and more evenly distributed across the brain; and 3) changes in neural noise and behavioral variability in response to different task demands and changes in the environment will be reduced.